2022
DOI: 10.3389/fpsyt.2022.809107
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Symptom Progression in School-Aged Children After COVID-19 Home Confinement: A Longitudinal Study

Abstract: BackgroundThe long-term mental health effects of coronavirus disease 2019 (COVID-19) in children are rarely reported. We aimed to investigate the progression of depressive and anxiety symptoms among a cohort of children in the initial epicenter of COVID-19 in China.MethodsTwo waves of surveys were conducted in the same two primary schools in Wuhan and Huangshi, Hubei province: Wave 1 from 28 February to 5 March, 2020 (children had been confined to home for 30–40 days) and Wave 2 from 27 November to 9 December,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…After deduplication, we assessed 24,926 abstracts for eligibility (see Figure 1). After the screening process, 191 studies were included in the systematic review 50,51,56–244 with a total...…”
Section: Resultsmentioning
confidence: 99%
“…After deduplication, we assessed 24,926 abstracts for eligibility (see Figure 1). After the screening process, 191 studies were included in the systematic review 50,51,56–244 with a total...…”
Section: Resultsmentioning
confidence: 99%
“…Considering the trajectories of depressive symptoms during the pandemic, the study results are mixed. Most studies ( n = 7) found that depressive symptoms increased (or remained elevated compared to pre-pandemic levels) during the pandemic in the studied populations ( 36–39 , 47 , 51 , 55 ). In a smaller study in Italy on children aged 5–6 years, Cimino et al ( 38 ) surprisingly only found an increase in the group of children with mothers not at risk of psychological problems, while there was no change in depressive symptoms in the at-risk group.…”
Section: Resultsmentioning
confidence: 97%
“…Nine of the 12 studies that investigated depressive symptoms also measured anxiety symptoms ( 5 , 36 , 39 , 47–49 , 51 , 55 , 56 ). One additional longitudinal study addressed anxiety but not depression in children and adolescents aged 8–18 years in Germany ( 42 ).…”
Section: Resultsmentioning
confidence: 99%
“…A national mental health study conducted in February and April 2020 among Chinese adolescents showed that the prevalence of depression and anxiety increased over time evidently ( Chen et al, 2021 ). The prevalence of depressive and anxiety symptoms among back-to-school children was elevated in comparison to that during the home quarantine period ( Xie et al, 2022 ). The prevalence of insomnia, anxiety and depression among high school students after reopening schools during the COVID-19 was 42.7 to 63.4% ( Puteikis et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%